Morphometric study of lumbar vertebral pedicles - Khatiwada, Sushma; Sudhin, Budhi Nath Adhikari; Pandey, Neeraj; Shrestha, Iju; Dhungel, Deepesh (Journal of Chitwan Medical College, 2021)
Background: Pedicle screw instrumentation has revolutionized spine surgery on account of its superiority over other stabilization systems. It is safe when properly placed and versatile for a range of procedure from fracture fixation to complex deformity correction. Sound anatomical knowledge of the pedicle may also be helpful during surgical approach to lumbar foramina disc herniation and epidural steroid injection as well as in the diagnosis of some lumbar degenerative diseases and chronic back pain. In this study we aimed to provide locoregional data on lumbar pedicle morphometry of Nepalese population. Methods: A descriptive observational study was conducted on 50 dry adult human lumbar vertebrae of unknown sex at Chitwan Medical College from August 2020 to December 2020. Pedicular width, height and the interpedicular distance were measured. All the data were numerally coded in excel and analysis was done in Statistical Package for Social Sciences (SPSS) version 20. Results: The mean width of the pedicles of left side gradually increased as we moved down the vertebrae and measured 7.43 ±0.84 mm in L1 and 12.18±1.71 mm in L5 vertebrae. The mean width of the pedicles on the right side, however, showed an increasing trend with a lower value at L3 level and was measured as 7.91± 1.17 mm. The mean height of the pedicles alternatively decreased and increased down the vertebrae for both the sides. The mean interpedicular distance gradually increased craniocaudally and was found to be 20.35±0.95 for L1 and 25.97±3.58 mm for L5 vertebrae. Conclusions: This study confirmed the measurement of lumbar pedicles’ dimensions and provides its regional data on Nepalese population. These data may be critical for clinicians working near the vicinity of the lumbar pedicles.